Palaeoenvironmental and palaeoclimatic reconstruction of the Witbank coal deposits (Karoo Basin South Africa) - Goetz, A.E. (Annette) (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.